PENGARUH MINAT DAN KEBIASAAN BELAJAR TERHADAP PRESTASI BELAJAR - Samben, Sarah (Pascasarjana Universitas Negeri Makassar, 2014)
The research objective was to determine the effect of interest and study habits of students towards mathematics learning achievement. The method used is the method of correlation analysis surveys in SMA EKSEKUTIF NUSANTARA, Makassar. Study sample as many as 28 students were drawn from a population with a sampling technique in accordance with proportion. Analysis of data using correlation and regression techniques. The results showed: (1) there positively influence students' interests and learning habits simultaneously learning achievement mathematics. (2) no influence students' interest in learning mathematics learning achievement. (3) no influence students' study habits Biology learning achievement.